The interactive effects of age, education, and BMI on cognitive functioning. Issue 2 (3rd March 2016) - Kirton, Joshua W.; Dotson, Vonetta M.
Abstract: We examined the moderating effects of age and cognitive reserve on the relationship between body mass index (BMI) and processing speed, executive function, and working memory based on the literature suggesting that obese individuals perform more poorly on measures of these abilities. Fifty-six healthy, dementia-free community-dwelling older (mean age 65.72 ± 7.40) and younger (mean age 21.10 ± 2.33) adults completed a neuropsychological battery and reported height and weight. Mixed effects models were used to evaluate the interactive effects of age, education (a proxy for cognitive reserve), and BMI on cognitive scores. Higher education was protective for executive deficits in younger, but not older adults. Age differences in executive functions were reduced at higher education levels but increased in individuals with higher BMI. Results suggest the inter-relationships between cognitive reserve – as measured by education – and BMI differ across age, and that obesity may accelerate the cognitive aging process.